1996
DOI: 10.1016/0895-7061(95)00394-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional echocardiography compared to two-dimensional echocardiography for measurement of left ventricular mass anatomic validation in an open chest canine model

Abstract: A three-dimensional echocardiographic system has been developed that can accurately compute left ventricular mass in vitro. This study was designed to validate the new echocardiographic system for the measurement of left ventricular mass in vivo and to compare the accuracy of three-dimensional echocardiography to the accuracy of conventional two-dimensional echocardiography for measuring left ventricular mass. Echocardiographic imaging was performed 6 h following coronary ligation in 20 open chest dogs, at whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Moreover, the inadvertent use of oblique cuts in M mode echocardiography and foreshortened apical views with 2DE can potentially result in additional inaccuracies. 6 14-17 Three dimensional echocardiography, as a basis for offline three dimensional reconstruction from multiple planes, has been shown to reliably quantify LV mass in both animal experiments [18][19][20][21] and human studies. 16 22 23 The enhanced accuracy with reduced interobserver variability has been obtained with a variety of methods for data acquisition, including the gated rotational approach 18 24 and freehand scanning with locator devices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the inadvertent use of oblique cuts in M mode echocardiography and foreshortened apical views with 2DE can potentially result in additional inaccuracies. 6 14-17 Three dimensional echocardiography, as a basis for offline three dimensional reconstruction from multiple planes, has been shown to reliably quantify LV mass in both animal experiments [18][19][20][21] and human studies. 16 22 23 The enhanced accuracy with reduced interobserver variability has been obtained with a variety of methods for data acquisition, including the gated rotational approach 18 24 and freehand scanning with locator devices.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that 3D techniques based on offline reconstruction from multiple planes, including rotational acquisition 3,14 and free-hand scanning with locator devices 13,15-17 and more recently followed by the early real-time volumetric imaging system, 18 were more accurate than the conventional M-mode or 2D methods. These studies and others have endorsed the use of 3D data as a more accurate way to evaluate LV mass on the basis of validation in animal experiments 3,5,7,14,16 and explanted human hearts, 6,15 with comparisons against true anatomic mass, and in vivo validation with CMR imaging. 4,5,10,11 In addition, several studies demonstrated that the 3D-based techniques are more reproducible and have less variation between observers than conventional techniques.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Previous studies have demonstrated the feasibility of this approach from 3D data reconstructed from consecutive multiplane acquisitions. [5][6][7] The recent development of real-time 3D (RT3D) imaging technology is especially appealing because it can potentially allow nearly online quantification of LV volumes and mass without the need for tedious reconstruction.…”
mentioning
confidence: 99%
“…Two-dimensional echocardiography (2DE) is the most widely used modality in daily practice, but measurements are not always accurate in patients with wall motion abnormality after remodeling, because of poor reproducibility and geometric assumptions [3]. Three-dimensional echocardiography (3DE) is expected, theoretically, to be more accurate [4], but few reports have compared the accuracy of 3DE with that of left ventriculography (LVG) in patients with abnormal wall motion. We investigated the reproducibility of the newly developed real-time three-dimensional echocardiography (RT3DE) and correlations of RT3DE and 2DE with LVG.…”
Section: Introductionmentioning
confidence: 99%